АРГУМЕНТАЦІЯ У СВІТЛІ КОГНІТИВНИХ ОПЕРАЦІЙ (на матеріалі німецького аргументативного дискурсу) - Пірог, Інна Іванівна (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2015)
The article deals with linguistic and cognitive mechanisms of argumentation formation. The main linguistic operations, taking part in the construct of argumentation, are described. They are: prominence, filling in pattems of contours, focusing, specificity, perspective. The dependence of the argumentation method on the cognitive operations nature are established.